Multiply Your Business Value Through Brand and AI. - Narayan, Rajan. (Studien Zum Physik- und Chemielernen Series, 2021)
This book presents the case for building brands effectively and optimally using AI, thereby enhancing the overall value of the organization. This book is ideal for entrepreneurs, investors, CEOs, and brand managers as it provides them with pathways of using AI to build brands and create value. It can be used as a textbook in courses on brand management and as a supplemental text in marketing management courses. It is especially relevant today, where many enterprises are being founded by non-marketing professionals.